Community Engagement in DHF Prevention: An Analysis of Variances in Knowledge and Behavior - Dina Fajarina; Meida Laely Ramdani (Proceedings Series on Health & Medical Sciences, 2024)
Background: Dengue Hemorrhagic Fever (DHF) is a disease that originates from the Aedes aegypti mosquito, especially in tropical areas. The spread of DHF is increasing, this is indicated by the high prevalence of the disease and the rapid increase in the number of DHF cases in Indonesia. Dengue fever cases will become the center of attention for health in Indonesia in the coming years. Objective: To find out differences in knowledge and behavior of dengue prevention in the community. Methods: This study uses a quantitative method with a case control design. The sampling technique used was total sampling with a total sample of 44 respondents, 22 groups had suffered from DHF and 22 groups had never suffered from DHF. The research was conducted in Ngalian Village, Wadaslintang District, Wonosobo Regency. Results: This study has an average knowledge of DHF prevention in people who have had DHF 7.36 and people who have never had DHF 8.36 Behavior of DHF prevention in people who have had DHF 19.31 , and people who have never had DHF 27 , after being carried out includes differences in knowledge and differences in dengue prevention behavior in the community in Ngalian Village, Wadaslintang District, Wonosobo Regency with a p-value of 0.005 (knowledge) and a p-value of 0.000 (behavior). Conclusion: This study shows that there are differences between the knowledge and behavior of DHF prevention in people who have had DHF and those who have not had DHF.